2022
DOI: 10.1111/jocn.16466
|View full text |Cite
|
Sign up to set email alerts
|

Ostomy‐related problems and their impact on quality of life of Saudi ostomate patients: A mixed‐methods study

Abstract: Aim and objective The aim of this study is to explore the health‐related quality of life outcomes and ostomy‐related obstacles among patients with ostomy in Saudi Arabia. Background Negative effects on quality of life for patients following ostomy creation are a globally important health concern. Paucity of understanding factors that influenced quality of care after ostomy surgery hinders the ability of healthcare providers to offer appropriate care to improve patient's quality of care. Methods This mixed‐meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…The study also showed that several patients experienced psychological and physical challenges regarding the stoma and needed assistance from health personnel, especially stoma nurses, for improved training and guidance [15]. This is in accordance with the findings of Alenezi et al (2022), who showed that counselling and guidance from competent nurses before and after the surgical stoma surgery are of crucial importance for better quality of life [16].…”
Section: Introductionsupporting
confidence: 83%
“…The study also showed that several patients experienced psychological and physical challenges regarding the stoma and needed assistance from health personnel, especially stoma nurses, for improved training and guidance [15]. This is in accordance with the findings of Alenezi et al (2022), who showed that counselling and guidance from competent nurses before and after the surgical stoma surgery are of crucial importance for better quality of life [16].…”
Section: Introductionsupporting
confidence: 83%
“…Three studies involving general surgical conditions during Ramadan included stoma care, superior mesenteric artery (SMA) syndrome, and sigmoid volvulus (SV). [41][42][43] The healthrelated quality-of-life outcomes and ostomy-related obstacles among patients with an ostomy in Saudi Arabia was examined in a mixed-methods study by collecting quantitative data (n ¼ 421) and semistructured interview for collecting qualitative data (n ¼ 12). 41 Patients with intestinal stomas demonstrated multiple health-related qualityof-life challenges, including interfering with religious practice, mainly RF and Hajj.…”
Section: Surgerymentioning
confidence: 99%
“…[41][42][43] The healthrelated quality-of-life outcomes and ostomy-related obstacles among patients with an ostomy in Saudi Arabia was examined in a mixed-methods study by collecting quantitative data (n ¼ 421) and semistructured interview for collecting qualitative data (n ¼ 12). 41 Patients with intestinal stomas demonstrated multiple health-related qualityof-life challenges, including interfering with religious practice, mainly RF and Hajj. Another study examined the clinical records of 416 consecutive cases of SV patients reviewed prospectively from January 1986 to July 2020.…”
Section: Surgerymentioning
confidence: 99%
“…6 The potential for ostomy surgery is a primary concern among many individuals with bowel disease; this worry has been reported to surpass concerns related to progress of the underlying disease itself. 7,8 Depression, social isolation, anxiety, 9,10 suicidal ideations, loneliness, sexual issues, 11 and loss of autonomy, dignity, and confidence 12 are associated with having an ostomy.…”
Section: Introductionmentioning
confidence: 99%